Symphysis-Fundal Height Curve in Pregnancies Complicated by Maternal Hyperglycemia: Comparison with Curves of Nondiabetic Pregnant Women - Basso, Neusa A. S. [UNESP]; Costa, Roberto A. A. [UNESP]; Dias, Adriano [UNESP]; Magalhães, Claudia G. [UNESP]; Rudge, Marilza V. C. [UNESP]; Calderon, Iracema M. P. [UNESP] (Wiley, 2020)
Background. Reference symphysis-fundal height (SFH) curves for pregnancies complicated by maternal hyperglycemia are not available. Objective. To build an SFH curve according to gestational age for pregnant women with hyperglycemia-type 2 diabetes (T2DM), gestational diabetes mellitus (GDM), or mild gestational hyperglycemia (MGH) and compare it with three other curves in use in Brazil. Methods. Prospective cohort study of 422 pregnant women with hyperglycemia attending the Perinatal Diabetes Research Center (PDRC) of Botucatu Medical School, São Paulo State University/UNESP. Between 13 and 41 weeks of pregnancy, 2470 SFH measurements were obtained (mean 5.85 per woman). For the assessment of glycemic control, 2074 glucose level measurements were taken and the glycemic mean (GM) at each gestational week was estimated. Results. GM was adequate (<120 mg/dL) in 94.9% and inadequate (≥120 mg/dL) in 5.1% of the cases. The equation applied for SFH prediction was expressed as SFH=1.082+0.966∗week (r2=84.6%). At visual analysis, P10 and P90 SFH measurements were higher in the study curve than in the three other curves. Statistical analysis confirmed that SFH median values in this study were higher than those in the reference curve of habitual risk pregnancies, especially after 19 weeks of pregnancy. Conclusion. Taking into account that the maternal hyperglycemia was at strict control, our unedited results suggest that the current SFH curve can be a useful tool in prenatal care of T2DM, GDM, and MGH pregnant women.